Statutory Rape: Case Characteristics When Offenders are Younger Than 21 Years of Age Versus Older - Lippert, Tonya (Journal of interpersonal violence, 2022)
Statutory rape laws are intended to protect adolescents from harm as a result of sexual activity with older individuals. In this pursuit, many, but far from all, states? statutory rape laws differentiate younger and older offenders. In effect, many of these states differentiate offenders who are 21 and older from those who are under 21. It is unknown, however, whether and how the dynamics of statutory rape vary depending on the age of the offender. To explore the contribution of offender age to the dynamics of statutory rape, data were collected from the records of 105 statutory rape cases referred to a child abuse assessment center over a 63-month period. Records included detailed reports on case history and victims? family history, mental health and health-risking behaviors, medical examination results, and forensic interview summaries. Cases of offenders11.Because these cases are under investigation, ?offenders? here refers to ?suspects.? For ease of reading, we use ?offenders? to be consistent with prior research terminology. under 21 were compared to the cases of offenders 21 years and older. Compared to cases of younger offenders, cases of offenders 21 years and older more often involved slightly older adolescent victims. Independent of age, victims with offenders 21 and over compared with offenders under 21 were over six times as likely to have a prior history of a high, versus low, number of psychosocial problems and were seven times more likely to experience multiple forms of coercion versus no coercion by the offender. Findings suggest that statutory rape prevention, policy and response strategies should consider the critical ways that case characteristics and victims differ according to this key offender attribute.